Association of State Medicaid Expansion Status With Hypertensive Disorders of Pregnancy in a Singleton First Live Birth. Issue 1 (January 2022) - Everitt, Ian K.; Freaney, Priya M.; Wang, Michael C.; Grobman, William A.; O'Brien, Matthew J.; Pool, Lindsay R.; Khan, Sadiya S.
Abstract : Background: Incidence of hypertensive disorders of pregnancy is increasing in the United States. Early detection is important to prevent adverse maternal and offspring outcomes. This ecological study evaluated changes in rates of hypertensive disorders of pregnancy among states that expanded Medicaid compared with states that did not expand Medicaid. Methods: A quasi-experimental analysis using difference-in-differences models compared changes in rates of hypertensive disorders of pregnancy in Medicaid expansion states relative to non-Medicaid expansion states from 2012 to 2019. Maternal data from singleton first live births to individuals aged 20 to 39 years were obtained from the National Center for Health Statistics. Outcomes of interest included age-adjusted rates of de novo hypertension in pregnancy (gestational hypertension or preeclampsia) and prepregnancy hypertension. Results: Data from 7 764 965 individuals with a singleton first live birth were analyzed from 17 states and Washington, DC that expanded Medicaid and 15 states that did not. Rates of de novo hypertension in pregnancy increased over the study period in both expansion (54.34 [95% CI, 48.25–60.43] to 74.87 [95% CI, 71.20–78.55] per 1000 births) and nonexpansion states (68.32 [95% CI, 61.02–75.62] to 84.79 [95% CI, 80.67–88.91] per 1000 births). In adjusted difference-in-differences analyses, expansion status was associated with a greater increase in rates of de novo hypertension in pregnancy (difference-in-differences coefficient, +8.18 [95% CI, 4.00–12.36] per 1000 live births) but a decline in rates of de novo hypertension in pregnancy complicated by low birth weight (−7.20 [95% CI, −13.71 to −0.70] per 1000 births with hypertensive disorders of pregnancy). In adjusted difference-in-differences analyses, there were no significant changes in rates of prepregnancy hypertension in expansion relative to nonexpansion states (+1.13 [95% CI, −0.09 to +2.35] per 1000 live births). Conclusions: Between 2012 and 2019, states that expanded Medicaid had a significantly greater increase in rates of de novo hypertension, with some evidence of better outcomes among those with de novo hypertension diagnosed in pregnancy. Abstract : Supplemental Digital Content is available in the text.